Research of Influence of Vibration Impact of the Basis in the Micromechanical Gyroscope; Recent Advances on Systems, Signals, Control, Communications and Computers, December 12-14, 2015, Budapest, Hungary - Galtseva (Gal’tseva) O. V. Olga Valerievna (2015, 2015)
Title screen